A new black species of Kamimuria (Plecoptera: Perlidae) from Shaanxi Province, China - Yan, Yanhua; Liu, Ruijun; Li, Weihai (Zootaxa, 2019)
A new species of the perlid genus Kamimuria Klapálek, K. flavimacula sp. nov. from Shaanxi Province of northwestern China is described based on the male, female, eggs. The new species has an unusual dark habitus. The relationships of morphological characteristics of the new species and similar congener are discussed.